2020
DOI: 10.1002/prot.25968
|View full text |Cite
|
Sign up to set email alerts
|

Structural compliance: A new metric for protein flexibility

Abstract: Proteins are the active players in performing essential molecular activities throughout biology, and their dynamics has been broadly demonstrated to relate to their mechanisms. The intrinsic fluctuations have often been used to represent their dynamics and then compared to the experimental B-factors. However, proteins do not move in a vacuum and their motions are modulated by solvent that can impose forces on the structure. In this paper, we introduce a new structural concept, which has been called the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Remarks need to be given also regarding the physical meaning associated with the adopted perturbation scheme (i.e., harmonic excitations with a random direction in the space-domain but with a well-defined frequency content in the time-domain). In the previous literature, different force application patterns have been applied in a static fashion to probe protein flexibility [ 41 , 42 ] and protein conformational changes [ 44 , 45 , 47 ]. The approach proposed here (i.e., applying random forces to the protein ANM in a dynamic fashion) is supposed to simulate the external perturbations to the protein structure mainly due to Brownian motions of the surrounding particles [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Remarks need to be given also regarding the physical meaning associated with the adopted perturbation scheme (i.e., harmonic excitations with a random direction in the space-domain but with a well-defined frequency content in the time-domain). In the previous literature, different force application patterns have been applied in a static fashion to probe protein flexibility [ 41 , 42 ] and protein conformational changes [ 44 , 45 , 47 ]. The approach proposed here (i.e., applying random forces to the protein ANM in a dynamic fashion) is supposed to simulate the external perturbations to the protein structure mainly due to Brownian motions of the surrounding particles [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the Introduction, the ANM has also been used to predict protein flexibility and conformational changes upon the application of external perturbations to the protein network [ 41 , 42 , 44 , 45 , 47 ]. This is usually done in a static fashion, meaning that dynamic effects are neglected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 36 Therefore, we believe that protein packing can yield insights into protein stability as characterized by entropies. Over the past several years, we have investigated protein packing 37 as an important consideration for dynamics, 38 , 39 where we have demonstrated that hinges in proteins can be identified immediately from the static structure to be localized within the least densely packed regions. The present study aims to examine protein packing as the basis for protein entropy.…”
Section: Introductionmentioning
confidence: 99%